Subacute thyroiditis following COVID-19 vaccination in a 67-year-old male patient: a case report - Melisa Şahin Tekin; Suzan Şaylısoy; Göknur Yorulmaz (Taylor & Francis Group, 2021)
Subacute thyroiditis is the most common cause of painful thyroid gland diseases. It is characterized by inflammation of the thyroid gland and usually occurs after viral upper respiratory tract infections. Coronavirus disease 2019 (COVID-19) can lead to subacute thyroiditis. There are also vaccine-related subacute thyroiditis cases in the literature. Here, we describe a 67-year-old male patient developing subacute thyroiditis following COVID-19 vaccination.